Intestinal malrotation with levocardia and Spondylo-costal dysostosis: A case report - Jain, Arihant; Solanki, Shailesh; Mahajan, J.K; Sharma, Arun; Dogra, Shivani (Journal of Neonatal Surgery, 2024)
Background: Intestinal malrotation with midgut volvulus is usually present in the neonatal period but can present at any age, and can be associated with various congenital anomalies. These congenital defects increase the morbidity of the disease per se and require a multidisciplinary approach. Case Presentation: The index case was an eight-month-old child with intestinal malrotation, situs inversus, levo-cardia, single ventricle, and Spondylo-costal dysostosis. Here, we discuss its presentation, treatment, challenges during management, and review of pertinent literature. Conclusion: The association of intestinal malrotation with situs inversus, levocardia, and SCD requires further reporting as well as genetic studies to understand its embryo pathogenesis. The multidisciplinary team is essential for the ideal treatment of this type of complex case.